1984
DOI: 10.1210/endo-115-3-936
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that Copper-Amino Acid Complexes Are Potent Stimulators of the Release of Luteinizing Hormone-Releasing Hormone from Isolated Hypothalamic Granules*

Abstract: Chelated copper has been previously shown to stimulate the release of LHRH from isolated hypothalamic granules. In this study, we evaluated the chelator specificity, the kinetic constants, and the characteristics of copper interaction with LHRH granules. LHRH granules were isolated from the median eminence area of adult male rats and then incubated in a buffered medium at 37 C. Release of LHRH into the incubation medium was assessed by RIA of LHRH remaining in the granules after incubation. It was found that C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

1984
1984
1992
1992

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…Copper is present in the hypothalamus in concentrations much greater than in blood (14,15), and in hypothalamic homogenates, copper is highly concentrated in synaptosomes (pinched-off axonal terminals) (16). We noted (4,5) …”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Copper is present in the hypothalamus in concentrations much greater than in blood (14,15), and in hypothalamic homogenates, copper is highly concentrated in synaptosomes (pinched-off axonal terminals) (16). We noted (4,5) …”
mentioning
confidence: 71%
“…Tsou et al (2) observed increased levels of luteinizing hormone-releasing hormone (LHRH) in the pituitary stalk of the rabbit after the systemic administration of cupric acetate. We showed (3)(4)(5) that copper, at a concentration within the range required for the activity of several copper-dependent enzymes (6)(7)(8)(9), markedly stimulates the release of LHRH from isolated hypothalamic granules. Based on these findings, we proposed (4) that copper plays a role in regulating LHRH release from LHRH neurons in the following manner.…”
mentioning
confidence: 97%
“…4). Furthermore, coincubation of iso lated hypothalamic granules with copper salts stimulates the release of GnRH [2,5].…”
Section: Discussionmentioning
confidence: 99%
“…Copper salts initiate pituitary luteinizing hormone (LH) release, probably by discharging gonadotropin-releasing hormone (GnRH) from the hypo thalamus, since systemic injection of copper acetate (CuAc) increases GnRH levels in pituitary stalk plasma of anesthe tized rabbits [42], and addition of copper salts to isolated hypothalamic granules stimulates GnRH release in vitro [2,5], Ovarian steroids are involved in copper-induced ovula tion in rabbits, since estrogen facilitates [38,41] and proges terone may inhibit [12] the action of copper. However, since steroids can act at both central and pituitary sites [1,6,34,40], their effects on GnRH release after CuAc administra tion are unclear.…”
mentioning
confidence: 99%
“…13] to study some of the molecular events involved in secretion. We [2,5,15,16] have previously demonstrated that copper is an extremely potent stimulator of the release of LHRH from isolated LHRH granules. The characteristics of this release process are such that release follows Michaelis-Menten equations for enzyme kinetics (the apparent Km for copper is 4-6 \iM and the V,mix is about 60% of the granule content of LHRH released in 6 min), and that chelated copper (particularly copper-amino acid complexes) rather than ionic copper is the active form of the metal.…”
Section: Wheaton and Mccannmentioning
confidence: 99%